Total quality management and knowledge sharing: Comparing Malaysia's manufacturing and service organizations - Cheah, Weng Choong; Ooi, Keng Boon; Teh, Pei Lee; Chong, Alain Yee Loong; Yong, Chen Chen (Asian Network for Scientific Information, 2009)
The aim of this study was to examine the difference between Malaysian manufacturing and service organizations with regard to the multidimensionality of TQM practices and the relationship of these practices to knowledge sharing behavior from middle management employees’ perspective. The empirical data for this study were collected from 208 middle management employees from Malaysian manufacturing and service organizations with a response rate of 62.01% (129 respondents) from the manufacturing firms and 37.98% (79 respondents) from the service firms. The finding indicated there was no significance difference between Malaysian manufacturing and service organizations in the level of TQM practices and knowledge sharing. The multiple regression analysis also indicated a stronger relationship for manufacturing firms than for service firms between TQM practices and knowledge sharing, particularly in relation to teamwork. Results should be an interest to the TQM managers and practitioners in Malaysia. This finding increased our understanding on the applicability of TQM practices and the association of these practices to knowledge sharing in both Malaysian manufacturing and service organizations. This study has contributed towards advancing the TQM literature with a better understanding of the perception of middle management employees of TQM practices and its association with knowledge sharing in both Malaysian manufacturing and service organizations.